Axiology of the implementation of European court of human rights’ judgements in Ukraine (subsidiarity) - Mishyna, Natalia V.; Мішина, Наталя Вікторівна; Мішина, Н. В. (Одеса : Видавництво «Юридика», 2023)
Nowadays the principle of subsidiarity is quite popular in Ukrainian scientific literature. In addition, it is also a popular topic for the authors of the quasi-scientific articles, which reveal the problems of the organization of public power. This provides the basis for the potential of this principle to be used to the maximum in Ukraine. Therefore, an important scientific direction is to study the content of this multifaceted principle.
Mishyna N. V. Axiology of the implementation of European court of human rights’ judgements in Ukraine (subsidiarity) / N. V. Mishyna // Європейські орієнтири розвитку України в умовах війни та глобальних викликів ХХІ століття: синергія наукових, освітніх та технологічних рішень : у 2 т. : матеріали Міжнар. наук.- практ. конф. (м. Одеса, 19 травня 2023 р.) / за заг. ред. С. В. Ківалова. – Одеса : Видавництво «Юридика», 2023. – Т. 1. – С. 276-279.
Keywords: human rights; the constitutional status of the individual; implementation of decisions of the European Court of Human Rights; decisions of the European Court of Human Rights; subsidiarity; the principle of subsidiarity; права людини; конституційне становище особистості; виконання рішень Європейського суду з прав людини; постанови Європейського суду з прав людини; субсидіраність; принцип субсидіарності; Research Subject Categories::LAW/JURISPRUDENCE